2009
DOI: 10.5964/ejop.v5i2.268
|View full text |Cite
|
Sign up to set email alerts
|

Age and motives for volunteering: Further evidence

Abstract: This work has explored the socioemotional selectivity theory (Cartensen, 1995) with the purpose of evaluating how people selectively optimize their activities involving social investments as they increase in age, investing more in self-relevant and emotionally meaningful goals. Specifically, the purpose of this study was to test hypotheses derived from the socioemotional selectivity theory regarding the effects of age on motives for volunteering. The Volunteer Functions Inventory (Clary et al., 1998) was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 32 publications
1
27
0
5
Order By: Relevance
“…Okun and Schultz (2003) found an inverse association of age with career and understanding motives, but a positive relationship between age and social motives. The observed relationships between age and volunteering motives remained unchanged even when other researchers statistically controlled for the effect of volunteering experience (Dávila and Díaz-Morales 2009). Omoto et al (2000) revealed that younger volunteers were motivated to develop social relationships with novel others, and older volunteers were motivated to show care and concern to the society.…”
Section: Volunteerism and Well-beingmentioning
confidence: 87%
“…Okun and Schultz (2003) found an inverse association of age with career and understanding motives, but a positive relationship between age and social motives. The observed relationships between age and volunteering motives remained unchanged even when other researchers statistically controlled for the effect of volunteering experience (Dávila and Díaz-Morales 2009). Omoto et al (2000) revealed that younger volunteers were motivated to develop social relationships with novel others, and older volunteers were motivated to show care and concern to the society.…”
Section: Volunteerism and Well-beingmentioning
confidence: 87%
“…М. Давила и Х. Диас-Моралес (M. Dávila, J. Díaz-Morales) показали, что существуют стандартные отклонения в мотивации для каждой возрастной группы [16]. Наиболее важный показатель для участников волонтерского движения всех возрастов -ценности.…”
Section: Introductionunclassified
“…The literature on what motivates individuals from different age groups to join and contribute in the volunteer service covered three continents: North America (Clary, et al, 1998) (Shrader, 2012), Australia (Francis & Jones, 2012), ) and Europe (Davila & Diaz-Morales, 2009) (Ferreira, Proenca, & Proenca, 2012). A broader question of why people choose to volunteer to undertake unpaid work of any kind was studied by Benson et al (1980) The model most commonly used in recent research appears to be Volunteer Functions Inventory (VFI) by Clary et al (1992) shown in Appendix 1.…”
Section: List Of Figuresmentioning
confidence: 99%
“…The second key implication from the study relates to young adult volunteers where recruitment and retention strategies may require, in order to maximize total motivation, some modifications, such as providing greater flexibility, empowerment and opportunities for younger members to satisfy career, status and success factors, in order to increase the likelihood of volunteer satisfaction and retention among this group (Francis & Jones, 2012 (Davila & Diaz-Morales, 2009). In general the findings from the study were consistent with the predictions, with some exceptions.…”
Section: List Of Figuresmentioning
confidence: 99%
See 1 more Smart Citation